Mitral Valve Prolapse - Gewillig, Marc; Budts, Werner; Flameng, Willem (SA Heart Journal, 2017)
Mitral valve prolapse (MVP) is the most common valvular abnormality, affecting 2.4% of the population. Usually MVP is a benign disease and remains asymptomatic. The diagnosis of MVP is based on clinical presentation, physical examination and echocardiography. Some atypical symptoms that are not correlated with mitral valve function, are described as the MVP syndrome. Potential complications such as infective endocarditis, thromboembolic events, atrial and ventricular arrhythmias, and progressive mitral valve regurgitation may occur. Management should concentrate on adequate guidance of the patients, relief of symptoms and avoidance of complications.